1997
DOI: 10.1046/j.1469-8137.1997.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

A stay‐green mutation of Lolium perenne affects NO3 uptake and translocation of N during prolonged N starvation

Abstract: SUMMARYApparent X,,, and I/,,,,, for net NO.," uptake and short-term translocation patterns of recently absorbed N were compared in a stay-green mutant and wild-type selection line of Lolium pereniie L, by means of a series of depletion studies using ''NO.," , performed over 12 d under conditions of progressively increasing N deprivation. In view of the greater retention of N in senescent leaves of the stay-green phenotype, it was predicted that NO^" uptake would he up-regulated relative to the nomial line, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Conversely, N deficiency causes an increase of NRT2.1 gene expresion (Gansel et al 2001). Circumstantial support for the involvement of the avilability of reduced N in the down regulation of N uptake was also provided by Bakken et al (1997), who reported that the higher V max for nitrate uptake observed in a 'staygreen' mutant of L. perenne is associated with a reduced availability of remobilized N, compared with a normal line. The putative role of cycling amino acids as a signal for the regulation of nitrate uptake is also supported by a rapid turnover of the prevalent xylem amino acid in L. perenne (Thornton and Macduff 2002).…”
Section: Introductionmentioning
confidence: 86%
“…Conversely, N deficiency causes an increase of NRT2.1 gene expresion (Gansel et al 2001). Circumstantial support for the involvement of the avilability of reduced N in the down regulation of N uptake was also provided by Bakken et al (1997), who reported that the higher V max for nitrate uptake observed in a 'staygreen' mutant of L. perenne is associated with a reduced availability of remobilized N, compared with a normal line. The putative role of cycling amino acids as a signal for the regulation of nitrate uptake is also supported by a rapid turnover of the prevalent xylem amino acid in L. perenne (Thornton and Macduff 2002).…”
Section: Introductionmentioning
confidence: 86%
“…If chlorophyll degradation is impaired, much of the N of thylakoids is unavailable for recycling. It follows that, when N supply is limited, stay-green plants pay a significant penalty compared with normally yellowing types in terms of rates of growth and development, because their internal N relations are compromised by a large pool of inaccessible protein in senescent leaves (Bakken et al, 1996;Hauck, 1996). In this sense, it is not an exaggeration to consider chlorophyll catabolism as a pace-setting process with implications for wholeplant development and ecological fitness.…”
Section: In Senescencementioning
confidence: 99%
“…The type of senescence, rapid or delayed, seems to be a dominant characteristic and has been observed in wheat (Boyd and Walker 1972) and maize (Crafts-Brandner and Poneleit 1992). Selection for the purpose of decreasing leaf senescence, which results in an extension of photosynthetic activity especially for transfer of carbohydrates to grain fill, seems much more promising than the increase of photosynthetic efficiency alone, especially because senescence is regulated by a smaller number of genes than photosynthesis (Nelson 1988;Bakken et al 1997).…”
Section: Traits Of Interest and Breeding Opportunities For High-tempementioning
confidence: 99%